DIONISO UMA REVISITAÇÂO AO SELVAGEM - Toledo, Tulio (Sacrilegens, 2019)
This paper seeks to analyze the symbolism present in the figures of Dionysos and Pentheus in Euripides tragedy, using the play as a hermeneutic key to understand the opposition between the feeling of the polis and the dionisiac natural experience, experienced by the mainades. The objective of this article is to understand the initiation to the cult of Dionysos Lysios as a possibility for a transformation of the individual and the form he comprehends himself in the world and acts before the natural space. Through a literary analysis, this paper proposes a revisitation to a condition where natura has not been externalized, that means, not separated from beings. It also seeks to understand the possibility of how the individual could experience a more harmonious relationship with the natural world within the polis, different from the mainades who sought shelter in the mountains. The civilized man faced with the problem of his detachment with nature, parts toward a possible reeducation of his gaze to expirience the wild environment proposed by Dionysos.